Sexual behavior of the digger wasp Sphex ingens Smith (Hymenoptera, Sphecidae) - Souza,Carlos Alberto S. (2015)
A species' mating system depends on its spatial distribution and temporal availability of mating opportunities, as well as on the resources that create these opportunities. In addition, for many species, courtship is driven by specific behaviors that precede and follow copulation. Although Sphex ingens is a taxonomically well known species of digger wasp, its ecology and behavior remain poorly known. Hence, we analyzed patterns and trends of sexual behavior, in order to understand whether courtship can persist in a polygamous mating system. We monitored by video wasp populations in Ilha Grande, southeastern Brazil. Based on the observed behaviors, we calculated stochastic probabilities with a Markov chain to infer on behavioral trends. We recorded four behavioral phases based on 19,196 behavioral acts observed in 224 copulation attempts. There were no significant differences in common behavioral acts between males and females. The copulation patterns, conflicts, and trends observed in S. ingens clearly show the influence of sexual selection in its promiscuous mating system.